PERSEPSI GURU MENGENAI SEX EDUCATION DI SEKOLAH DASAR KELAS VI - Panjaitan, Regina Lichteria; Djuanda, Dadan; Hanifah, Nurdinah (Universitas Pendidikan Indonesia, 2015)
The role of technology, especially information technology in Indonesia in the building society XXI century. Indonesia has begun to enter the stage of the telematics community will certainly have a major impact on all levels of life of the Indonesian nation, especially in children. The emergence of a great revolution throughout the world of children's playground, Internet presence replaces the open airy space for children's play, besides presenting impression's Internet pornography and violence can harm the development of children's personality. Sexual deviance behavior at the level of schooling is quite surprising, of course. This is a challenge for education and should be used as a rationale for the need for innovation in learning. Things into consideration are for this. Sex education in early childhood is considered taboo in society. Guru is one of the determining factors of high and low quality of education has a strategic position in transforming sex education to learners. Therefore, this study tries to analyze how perceptions of teachers on sex education at the primary school level, the research method used is a descriptive method.Keywords: Perception of teachers, sex education, learners in primary schools.